Asuhan Keperawatan pada An. A dengan Post Operasi Limpadenopati di Ruang Mawar 2 RSUD Dr. Soeselo Kabupaten Tegal - Hilda Erliana; Ahmad Zakiudin; Sukirno Sukirno (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Lymphadenopathy is a condition characterized by the enlargement of lymph nodes, commonly encountered in clinical practice, and may indicate both infectious and non-infectious disorders. This condition often causes anxiety as it is frequently associated with chronic diseases or malignancies. This study aims to describe nursing care in patients with lymphadenopathy through a case study approach and theoretical review. The method used was a descriptive case study with data collected through interviews, physical examinations, observations, and documentation. The results revealed the main complaint of pain in the anterior neck following surgical intervention. The identified nursing diagnoses included acute pain, knowledge deficit, and risk of infection. Interventions were carried out in the form of infection prevention, pain management, and health education. Evaluation showed significant improvements. The study concludes that comprehensive nursing care for patients with lymphadenopathy is effective in reducing symptoms, alleviating anxiety, increasing patient knowledge, and positively impacting quality of life.